معايير تمييز القرار الإداري في الفقه والقضاء دراسة مقارنة (سوريا, مصر, فرنسا) - نوح مهند; اسماعيل شادي (Latakia University Journal - Economic and Legal Sciences Series, 2013)
كان للانتقال إلى مبدأ فصل السلطات بمفهومه النسبي أثر واضح في تحقيق الخلط بين الأعمال القانونية لسلطات الدولة, فكان لا بد من البحث عن معيار واضح يحدد الطبيعة القانونية لتلك الأعمال, خاصة وأنها تتمايز من حيث النظام القانوني الذي يحكمها. وتبرز أهمية هذا المعيار في تمييز القرارات الإدارية عن غيرها من الأعمال الأخرى التي تأتيها سلطات الدولة كأداة فعالة بيد الإدارة لممارسة سلطتها في مواجهة الأفراد, كونها تخضع لرقابة القضاء من جهة, وتعد قابلة للإلغاء والتعديل من قبل الإدارة من جهة أخرى, إضافة لمسؤولية الدولة عما تلحقه تلك الأعمال من ضرر بالأفراد, فيترجح الفقه والقضاء في ذلك بين معيارين, وإن رجح أحدهما على الآخر, لذا يهدف هذا البحث إلى تبيان المعيار المستخدم في تمييز القرار الإداري عن غيره من الأعمال القانونية, وموقف الفقه والقضاء السوري المصري والفرنسي من ذلك. The move to the principle of separation of powers in its relative meaning has a clear impact in achieving the confusion between the legal works of the state authorities. Therefore, it was necessary to search for clear criteria to identify the legal nature for those works, especially that they differ in terms of the legal system governing them. These criteria are important in distinguishing the administrative decisions form the other works which the state authorities do, especially that they are an effective tool within the hand of the administration in the face of individuals being subject to the judicial control on the one hand, and that they are liable to be canceled and modified by the administration on the other hand. In addition, the state is responsible for the harm caused by these acts to individuals. The jurisprudence and the judiciary are swinging between the two criteria even if one of them overshadows the other. This research aims to demonstrate the criteria used in distinguishing the administrative decision from the other legal works, as well as the standpoint of the Syrian, Egyptian and French jurisprudence and judiciary regarding this issue.